The impact of the method of genetic identity disclosure on the donor conceived adult - Emily Ann Glidden; Dylan Thibaut; Jerry Goodman (Taylor & Francis Group, 2022)
Aim: 106 donor conceived people (DCP) responded to an anonymous survey study that examined the impact of the method of genetic identity disclosure and age at the time of the disclosure on their emotional wellbeing, familial relations, and perceptions of donor conception practices. Methods: Participants were asked to select the way in which they were informed they are DCP and the age group at which this occurred, and then were asked to select strongly agree, agree, neither agree or disagree, disagree, or strongly disagree in response to 26 statements that examined their perceptions of the topics listed above. Responses were grouped based on the age of genetic identity disclosure and the method of genetic identity disclosure, then numerically compared by assigning each type of response a number. Statistical analysis using repeatedmeasures ANOVA was performed to identify differences among these factors. Results: This analysis revealed that most participants 18 ≥ years and most participants who discovered their genetic identity through means other than through their parent(s) had worse emotional wellbeing and familial relations. However, most participants among all categories had a negative perception of donor conception practices. Conclusion: Continued work is needed to understand and support the growing DCP population.